استخدام مواقع التواصل الاجتماعي عبر الهاتف النقال و علاقتها بالاغتراب النفسي لدى الطلبة الجامعيين - فريال خرصي; اكرام بن السايح; د/ عهطالله طريف (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة: جاءت الدراسة بعنوان "استخدام مواقع التواصل الاجتماعي عبر الهاتف وعلاقتها بالاغتراب النفسي للطلبة الجامعيين"، وانطلقت من إشكالية مفادها: إلى أي مدى يسهم الاستخدام المتكرر لشبكة الفايسبوك في تنمية مشاعر الاغتراب النفسي لدى طلبة العلوم الإنسانية؟ وكيف تتجلى هذه العلاقة من خلال أنماط الاستخدام وأبعاده النفسية والاجتماعية؟، بهدف التعرف على مدى مساهمة الاستخدام المتكرر للفيسبوك في تعميق الشعور بالاغتراب النفسي لدى الطلبة، والكشف عن أبعاده النفسية والاجتماعية. اعتمدت الدراسة على المنهج الوصفي، وتم استخدام الاستبيان كأداة لجمع البيانات، وطبقت على عينة من طلبة الماستر بقسم الإعلام والاتصال بكلية العلوم الإنسانية والإسلامية والحضارة بجامعة عمار ثليجي بالأغواط، والبالغ عددهم 100 طالب (50 طالبة و50 طالبًا).وقد توصلت الدراسة إلى النتائج النهائية التالية: - أن الاستخدام المكثف والمتكرر لشبكة الفايسبوك يسهم في تنمية مشاعر الاغتراب النفسي لدى الطلبة. - تظهر العلاقة بين الاستخدام والاغتراب من خلال أنماط التفاعل الافتراضي وضعف العلاقات الواقعية. - يرتبط ارتفاع مدة ودوافع الاستخدام بزيادة حدة الشعور بالاغتراب النفسي. - وجود ضعف في الوعي بخطورة هذا الشعور بين أفراد العينة. - ينعكس الاغتراب في صور أبرزها: العزلة، التهميش، فقدان الانتماء، وتضاؤل التفاعل الاجتماعي الواقعي. Study Summary The study was titled "The Use of Social Media via Mobile Phones and Its Relationship with Psychological Alienation among University Students." It stemmed from the central question: To what extent does frequent use of Facebook contribute to the development of psychological alienation among students in the humanities? And how is this relationship manifested through usage patterns and its psychological and social dimensions? The study aimed to explore the extent to which repeated use of Facebook contributes to deepening feelings of psychological alienation among students and to identify the relationship between usage and its psychosocial effects. The study adopted the descriptive method, using a questionnaire as the data collection tool, and was conducted on a sample of Master’s students from the Department of Media and Communication, Faculty of Humanities, Islamic Studies, and Civilization at Amar Telidji University of Laghouat, totaling 100 students (50 male and 50 female).The study reached the following final results: • Intensive and frequent use of Facebook contributes to increasing feelings of psychological alienation among students. • The relationship appears through virtual interaction patterns and weakened real-life relationships. • Higher usage duration and motivations are associated with more intense feelings of alienation. • Students show limited awareness of the risks related to psychological alienation. • Alienation is manifested in forms such as isolation, marginalization, lack of belonging, and reduced real-life social interaction.
دراسة ميدانية على عينةمن طلبة الماستر بقسم الاعلام و الاتصال